Studies on Optical Activity, X-ray and Electronic Characteristics of 4-(4-Chlorophenylazo)- 2-(p-tolylimino-methyl)phenol - Sheikhshoaie, Iran; Mostafavi, Ali; Monadi, Niaz (Asian Journal of Chemistry, 2010)
The bidentate monoazo Schiff base compound 4-(4-chlorophenylazo)-2-(p-tolyliminomethyl) phenol Schiff base compound was prepared and characterized by several spectroscopic methods. In the present study 4-(4-chlorophenylazo)-2-(p-tolylimino-methyl) phenol Schiff base compound has been investigated by X-ray analysis and AM1 semiempirical quantum mechanical method. The crystal is in the monoclinic space group pc with a = 19.450(4) Å, b = 6.941 (10) Å, c = 6.116 (13) Å, dcalc.= 1.415 g/m3, V = 821/2 (3) Å3, α = 90º, β = 95.927º, γ = 90º and R = 0.0650 for 2408 independent reflections. The title compound has an intermolecular hydrogen bonding, N…H––O 2.550 Å between H (1) and N (3) atoms. The geometry data of the title compound were investigated by AM1 semiempirical quantum calculation. The optimized geometry of the molecular structure corresponding to the planar conformation and the computed structural data of the isolated molecule are compared with the experimental data. The AM1 optimization geometries of the Schiff base are in agreement with the crystallographic data. In the next part of this study the first hyperpolarizability (βμ) for 4-(4-chlorophenylazo)-2-(p-tolylimino-methyl) phenol Schiff base compound was calculated by using AM1 semi-empirical method. The calculated hyperpolarizability (βμ) for this compound is 31.4 times that of urea so this Schiff base compound has a good nonlinear optical property.